Comparative assessment of antimicrobial, antiradical and cytotoxic activities of cannabidiol and its propyl analogue cannabidivarin - Chiara Russo (Nature Portfolio, 2021)
Abstract Cannabidiol and cannabidivarin are phytocannabinoids produced by Cannabis indica and Cannabis sativa. Cannabidiol has been studied more extensively than its propyl analogue cannabidivarin. Therefore, we performed a battery of in vitro biological assays to compare the cytotoxic, antiradical and antibacterial activities of both cannabinoids. Potential mitochondrial metabolism alterations, DNA synthesis inhibition, and plasma membrane damage were studied by MTT assay, BrdU-ELISA and LDH assay of cancer and normal human cells exposed to cannabinoids. ABTS and DPPH assays were performed to observe the effects of the cannabinoids on free radicals. Microbial susceptibility tests were performed to study the activity of the cannabinoids in two bacterial species implicated in human infections, Escherichia coli and Staphylococcus aureus. The results showed that the cannabinoids induced medium levels of cytotoxicity in cancer and normal cells at concentrations ranging from 15.80 to 48.63 and from 31.89 to 151.70 µM, respectively, after 72 h of exposure. Cannabinoids did not exhibit a strong antioxidant capacity in scavenging ABTS or DPPH radicals. No evident differences were observed between the two cannabinoids in antimicrobial activity, except with respect to S. aureus, which showed greater susceptibility to cannabidiol than to cannabidivarin after 72 h of exposure.